2008
DOI: 10.3846/1648-6897.2008.16.151-158
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Potential of Mineral Magnetic Measurements as a Soil Particle Size Proxy/Magnetinių Mineralų Matavimų, Siekiant Jais Pakeisti Granuliometrinės Sudėties Analizę, Problemos Ir Potencialas/ Проблемы И Потенциальные Возможности Применения Магнитных Измерений Минералов Для Замены Анализа Гранулометрического Состава Почвы

Abstract: Abstract. The use of mineral magnetic concentration parameters (χ LF , χ ARM and SIRM) as a potential particle size proxy for soil samples collected from the Isle of Man (British Isles) is explored as an alternative means of normalizing particle size effects. Comparison of soil-related analytical data by correlation analyses between each magnetic parameter and individual particle size classes (i.e. sand, silt and clay), more discrete intervals within classes (e.g. fine sand or medium silt) and cumulative size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…Moreover, Booth et al [16] suggested χ LF , χ ARM and SIRM have potential as a particle size proxy for several sedimentary environments, but highlights the importance of fully determining the nature of the relationship between sediment particle size and magnetic properties before applying mineral magnetic data as a size proxy. More recently, this was further explored by Booth et al [27] who discussed potential problems of employing this technology. When data presented here are compared to these earlier investigations, it is apparent that the trends observed are mostly similar to previous studies (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Booth et al [16] suggested χ LF , χ ARM and SIRM have potential as a particle size proxy for several sedimentary environments, but highlights the importance of fully determining the nature of the relationship between sediment particle size and magnetic properties before applying mineral magnetic data as a size proxy. More recently, this was further explored by Booth et al [27] who discussed potential problems of employing this technology. When data presented here are compared to these earlier investigations, it is apparent that the trends observed are mostly similar to previous studies (e.g.…”
Section: Resultsmentioning
confidence: 99%